\(Arisaema vietnamense\) (section \(Nepenthoidea\), Araceae): a new species from Vietnam - Luu, Hong Truong; Nguyen, Hieu Cuong; Nguyen, Tran Quoc Trung; Nguyen, Quoc Binh (Academia Journal of Biology, 2022)
Arisaema vietnamense is described as a new species from Pu Ta Leng Mountain in Tam Duong District of Lai Chau province. This find expands the hitherto Sino-Himalayan distribution of Arisaema sect. Nepenthoidea southwards to Vietnam, adding to the six sections with twenty six species already known for the country. The new taxon is described and illustrated with field photographs of detailed botanical characteristics.